Reconsidering Hinduism: between reality and friction - Martino, Gabriel (2025)
In this paper, we examine the category of Hinduism and the main recent tendencies in academic studies of the subject. After a brief review of the results of two contemporary sociological studies on India, we analyze the arguments of scholars who claim the non-existence of a religion called “Hinduism”. The stance of those who emphasize the modern and constructed nature of the notion of Hindu religiosity, studies that highlight the diversity of traditions labeled as Hindu, and those that find unifying trends within them, as well as the challenges associated with considering Hinduism as a religion. Our aim is to highlight the complexity not only of the field of study but also the approaches that study them. We offer a nuanced critical proposal to rethink Hinduism without denying its realities or the frictions involved in its conceptualization.